2015
DOI: 10.1123/ijspp.2014-0315
|View full text |Cite
|
Sign up to set email alerts
|

Running-Intensity Fluctuations in Elite Rugby Sevens Performance

Abstract: The findings suggest that running intensity varies between and within halves; however, the index used will influence both the magnitude and the temporal identification of peak periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
58
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 0 publications
2
58
2
1
Order By: Relevance
“…An evaluation of running intensity and energy demands in Rugby-7s resulted in a recommendation that training drills should replicate the physiological demands experienced in matches 31 32. Earlier substitution of fatigued players in matches may also help to reduce the incidence of injuries; therefore, the use of rolling substitutions, which is being trialled by World Rugby, could contribute to a reduction in fatigue levels.…”
Section: Discussionmentioning
confidence: 99%
“…An evaluation of running intensity and energy demands in Rugby-7s resulted in a recommendation that training drills should replicate the physiological demands experienced in matches 31 32. Earlier substitution of fatigued players in matches may also help to reduce the incidence of injuries; therefore, the use of rolling substitutions, which is being trialled by World Rugby, could contribute to a reduction in fatigue levels.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the acceleration/deceleration demands of this position are substantially lower than that of halves and hookers (Table 3) If athletes are to be adequately prepared for the most intense periods of competition, training prescription should account for the acceleration-based running requirements common to rugby league. The novel methodology of the present study may attenuate this implication, in comparison to that of previous research, where the metabolic power method was used to describe the mean Pmet sustained in range of team sports, such as rugby sevens (~10 W·kg -1 ) 11 , soccer (~8 W·kg -1 ) 9 , rugby league (~9 W·kg -1 ) 12 and AFL (~10 W·kg -1 ) 10 . However, these values represent whole-match averages, and fail to account for the peaks in running intensity imposed on players throughout a match.…”
Section: International Journal Of Sports Physiology and Performancementioning
confidence: 91%
“…Recently, Furlan et al 11 utilized a 2-min moving average, to determine the peak periods of Rugby Sevens performance. The authors observed that relative distance underestimated the intensity of the identified peak period when compared to the Pmet, calculated using the methods of Gray 21 , which suggests the incorporation of acceleration-based methods are necessary when quantifying team sport movement demands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead of observing relative running distance over a whole game, peak relative running distance over shorter game intervals (e.g. a 2 min period) or metabolic power may be used as more discriminating measures (Furlan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%